Governança de TI da fundação de economia e estatística: um estudo para implantação da governança da tecnologia da informação em uma fundação pública de pesquisa - Goldberg Júnior, Valter Helmuth (Universidade do Vale do Rio dos Sinos, 2011)
Governance of Information Technology is one of the fundamental tools in corporate management and in continuous improvement of services and products. The primordial goal of this work was to identify which are the main IT objectives in which one public research foundation should invest to add value indicators and analyses in economics, sociology and statistical to deliver to society. By identifying key objectives from the standpoint of the organization's management, and linking the processes required by the array of goals, processes of COBIT 4.1, it was possible to obtain a vision of what the main IT processes are from the perspective of stakeholders. Integrating this vision into Moore´s model to add value to non-profit organizations, one achieves a way to deploy or redesign processes and measure results. Therefore it is possible to get information to define a strategic plan for IT that meets the main demands of the organization.
Keywords: Alinhamento; COBIT; Modelo de Moore; Processos de TI; Objetivos de TI; Alignment; COBIT; Moore model; IT processes; IT goals